An attractive but rarely seen Odontoglossum (Orchidaceae: Oncidiinae) from Ecuador - Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2015)
A new species of Odontoglossum from a limited area in western Ecuador is described, illustrated with a line drawing and color photographs, and compared with apparently closely related species, which are illustrated with color photographs. The new species differs from them all by a combination of features, such as the limited geographic distribution, frequently purple mottled pseudobulbs, a broadly pandurate lip lamina and widely spreading purple striped callus keels on the lip.